Toda-Yamamoto Granger No-causality Analysis of Stock Market Growth and Economic Growth in Ghana - Inusah, Nasiru; Inusah, Nasiru (Journal of Accounting, Business and Finance Research, 2018)
The paper aims at examining the causal nexus between stock market growth and economic growth in the context of Ghana for a sample period covering 1990 to 2016. Toda-Yamamoto (1995) Granger no-causality test which permits Granger causality test irrespective of the order of integration of the variables involved is employed in this study. Data used for the study is annual time series data covering the sample period. The study finds that GDP growth Granger causes stock price index (SPI) and stock value traded (SVT) but does not granger causes market capitalisation (MC). However, none of the stock market growth indicators (MC, STV, and SPI) Granger causes economic growth. Thus the findings of this study support economic growth-driven stock market growth. It is recommended that, in other to enhance the effect of stock market growth on economy, firms in the sectors of the economy that contribute significantly to GDP growth in the stock market should be encouraged, motivated and supported to participate in the stock market by listing on the stock market. Also, government should ensure stable macroeconomic and microeconomic environment for businesses that are listed on the stock market to flourish since stock market growth is found to be economy-driven.